Fuzzy Dark Matter from String Theory - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter, we will examine an alternative to the usual Λ CDM model, where the cold dark matter is replaced by a “fuzzy dark matter”, and we will see that it appears more naturally in string theory. In fact, it is based on the axionic models from the previous chapter.